Rancangan Garap Karya Gending Sekar Jagad Berbasis Motif Batik Gaya Yogyakarta - Umilia Rokhani; Haryanto Haryanto (Institut Seni Indonesia Yogyakarta, 2020)
The creation of works employing transforming media becomes an exciting breakthrough in the art industry to study. Using the concept of changing the media, the meeting of the two different media, such as art and music, provides opportunities for the emergence of a broader range of creative work. The design of musical works based on the inspiration and philosophy from the media of batik has complexity and beauty and high value as the great works from the Indonesian ancestors. Sekar Jagad is a title for the composition of musical design, taken from the name of a batik motif that is very familiar in Javanese culture. By understanding the basic batik motifs such as gringsing, kawung, machete, nitik, cement and poleng, the elements of vocal melodies performed in two different voices gave an overview of the concept of the Sekar Jagad batik motif. It indeed required knowledge of the shape, function and character of the batik motif itself as the basis for gending in musical arts. The melody arrangement was made entirely with two tunings or pelog and slendro scales. It was intended to find the characters that best suits the characteristics and philosophy of batik. The elements of batik motifs that were put together into one Sekar Jagad batik motif were then applied through vocal melodies and supported by lyrics that described some of these batik elements.